Is subclinical anxiety an endophenotype for bipolar I patients? A study from a Costa Rican sample - Contreras Rojas, Javier (2009)
Although genetic influences on bipolar I disorder are well established, localization of genes that predispose to the illness has been difficult. Some genes predisposing to bipolar I disorder may be transmitted without expression of the categorical clinical phenotype. One strategy to overcome this obstacle is the use of quantitative endophenotypes, as has been done for other medical disorders. Methods. We analyzed 30 bipolar I extended families (300 subjects, average family size 10.34 members, range: 2–31) and 20 unrelated healthy controls from a Costa Rican sample. Heritability and genetic correlation of the state and trait scale from the Anxiety State and Trait Inventory was computed by using the general linear model (SOLAR package software). We also assessed variation of both scores among groups (patients, relatives and controls) and tested independence of affection status. Results. Heritability for state is 0.45 (SE = 0.11, p = 0.0000001) and for trait is 0.89 (SE = 0.06, p = 6.22e− 29). Genetic correlation for state and trait is 0.29, (SE = 0.12, p = 0.038–3.19e− 8). Bipolar I patients showed the highest trait score (F = 12.17 [5,24], p = 0.002), (bipolar I patients > relatives with other pathologies, > healthy relatives > unrelated healthy controls) with normal distribution in healthy individuals and no difference regarding depression and mania current status, (F = 0.230, df = 1, p = 0.632 and F = 1.401, df = 1, p = 0.238, respectively), contrary to the state score. Limitations. Confounding factors such as comorbid disorders could affect the interaction of subclinical anxiety with mania. Due to our limited budget we were not able to re-evaluate the subjects and conduct a test retest to assess the STAI reliability and mood state independence of anxiety traits over different times. Further research is needed to evaluate if anxiety traits are specially related to bipolar I disorder in comparison with other traits such as anger, attention or response inhibition deficit, pathological impulsivity or low self-directedness. Conclusions. Anxiety state and trait are heritable and share some genetic factors but only trait showed normal distribution in healthy subjects, mood current status independence and significant liability for bipolar I disorder. A stair-step distribution of trait anxiety scores in the family members and controls based on their genetic proximity to affected individuals and diagnostic status suggests that trait anxiety could be an endophenotype in these bipolar I families.